Hidrotalcitas de Ni-Mg-Al como precursores de catalisadores para produção de gás de síntese a partir de biogás - Pedrotti, Wagner (2010)
Catalysts obtained by thermal decomposition of the precursors with hydrotalcite-like structure [Mg1-xAlx (OH)2]x+ [CO3]x/n. mH2O and [Ni1-x Mg1-xAlx (OH)2]x+ [CO3]x/n. mH2O were prepared, characterized and tested in the reactions of dry and oxidative reforming of methane. The precursors were modified with the addition of nickel during the precipitation or by impregnation, in order to increase the thermal stability and dispersion of the active metal and the resistance against carbon deposition during the reaction. The catalyst precursors were characterized by X-ray diffraction, thermal and gravimetric analysis, atomic emission spectroscopy, surface area determination (BET method) and temperature programmed reduction. The results indicated that the precipitation method led the formation of the hydrotalcite-type structure and that the variation in the calcination temperature resulted in mixed oxides with the desired structure: at 650 °C the mixed oxides were formed, but when the calcination temperature was increased to 850 °C these oxides had become more stable. It was observed in the catalytic experiments that the addition of different amounts of magnesium influenced the activity and stability of the oxides, when compared with samples that contained only Ni/Al. The mixed oxide with composition 12.67% Ni-Mg1,35/Al was the more active and resistant to deactivation during the reaction.